Social and Economic Impacts of Supply Chain Performance Measurement and Productivity with Particular Reference to Iraq - Al-Mehannah, Hind Ghanim; Jasim, Fatin Ayid; Hashim Al-Mousawi, Hanan Abdulkhudhir (ExcelingTech, 2019)
A lot of countries suffer from the large size of the informal economy as some estimates suggest that the volume of the informal economy in the economies of developing countries, represents a range from a high percentage of (30% -70%) of the gross domestic product of these countries. It means that a large proportion of economic activities in developing countries is operated with a level less than optimal level of operation and with high cost, which limits the benefit from the resources and energies available to these facilities that operate within this economy. In the 1980s, we witnessed the deployment of a number of new production strategies, such as timely production, lean manufacturing, Kanban systems and comprehensive quality management. These new production strategies were used by a number of companies to improve the management system, increase production and improve process quality, and reduce waste production and inventory costs, in order to improve competition in various markets. Recently, while these strategies focus more on improving supply chain management to achieve their goals, henceforth a number of developed supply chain management strategies can be analyzed with the help of a computer. Choice-based decision support tools play a crucial role in collaborating and managing decision support markets from a set of multiple component supply chains. This study concludes that the reason for the spread and growth of informal economy is related to economic, social and legal factors, which include the lack of employment opportunities that have resulted from decrease in the number of projects in public and private sectors and their limitations as well as some obstacles, the most important of which, is the expansion of financial and administrative corruption. In addition to that, the high volume of the informal economy has positive effects and other negative ones that exceed the positive effects on economy, and the most important of these effects are tax evasion, lack of social protection for workers, and deformation of data and statistics. Therefore, this study has recommended that state should give more attention to this economy by collecting and analyzing data and information on the labor market, preparing studies that show its economic feasibility, enhancing and expanding the extension of social protection, health, and occupational safety, improving governance climate in the country, strengthening the ruling of law and the legislations of labor law, improving the business environment for micro and small enterprises, establishing industrial and commercial complexes, facilitating the extraction of activity licenses, investing in education, and developing vocational training centers.